2011
DOI: 10.1007/s00468-011-0630-2
|View full text |Cite
|
Sign up to set email alerts
|

Functions and origin of plasmids in Erwinia species that are pathogenic to or epiphytically associated with pome fruit trees

Abstract: The genus Erwinia includes plant-associated pathogenic and non-pathogenic species. Among them, all species pathogenic to pome fruit trees (E. amylovora, E. pyrifoliae, E. piriflorinigrans, Erwinia sp. from Japan) cause similar symptoms, but differ in their degrees of aggressiveness, i.e. in symptoms, host range or both. The presence of plasmids of similar size, in the range of 30 kb, is a common characteristic that they possess. Besides, they share some genetic content with high homology in several genes assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 87 publications
0
25
0
1
Order By: Relevance
“…y Pseudomonas sp. (Llop et al, 2012;Behlau et al, 2012). Otros casos de resistencia a productos como kasugamicina y validamicina Additional key words: Passiflora edulis Sims, antimicrobial, resistance.…”
unclassified
“…y Pseudomonas sp. (Llop et al, 2012;Behlau et al, 2012). Otros casos de resistencia a productos como kasugamicina y validamicina Additional key words: Passiflora edulis Sims, antimicrobial, resistance.…”
unclassified
“…Plasmid extraction and restriction analysis confirmed that the plasmid had not integrated into the chromosome or undergone rearrangement under our experimental conditions, demonstrating its stability. Although most Erwinia species from pome fruits have plasmids of similar sizes in variable numbers of copies (27), specific E. piriflorinigrans sequences were selected for the new PCR protocols. The primers and probe designed did not amplify E. pyrifoliae or E. amylovora, or other closely related species that harbor similar-size plasmids, as templates.…”
Section: Discussionmentioning
confidence: 99%
“…According to Llop et al (2012), plasmids contain versatile bacterial genomes, and acquisition of extra-chromosome genetic elements is an important source of genetic diversification in phytopathogenic bacteria. Plasmids can be transferred between strains, species, and genera, and then passed down through the bacterial strain.…”
Section: Discussionmentioning
confidence: 99%